Web based 4G Drive Tests Post Processing Software for Educational and Enterprise Purpose - DEUSSOM DJOMADJI Eric Michel; KABIENA IVAN, Basile; CHIEGUE TCHUINMOGNE , Herman Yves (European Journal of Applied Sciences, 2022)
In the world of digital communications, we usually use terms as processing and network optimization. Because mobile operators continuously want to provide the best network experience and quality of service to their subscribers, they continuously seek to improve their network performance both in Coverage, Quality and performance. When mobile technology such as LTE is offered to the public, operators need to be certain that it satisfies their customers. The technology then needs to be tested and optimized if it does not meet the purpose. In this context, one will propose a tool for the processing of drive test data. The proposed tool can be used for enterprises and academic purposes. In fact, online educational courses have brought great dynamics in the field of education and research. It has revolutionized the way learning is being done and perceived in our society compare to traditional learning method. During this period of Covid-19 e-learning is developing faster than before and new solutions to improve it are proposed. For many sub-Saharan African countries, it is very scarce to find telecommunication lecturers with a PhD grade and this has an impact on quality of the training provided to students in telecommunications engineering fields. Another problem is the lack of means to buy and install telecommunication equipments for laboratory experimentations where students can learn and improve their skills during their training program in a university or college. To overcome these problems, a possible solution could be the design of efficient web based tool like the one proposed in this paper and implement labs and e-labs in other to enable students to have a better understanding of mobile network, drive test data post processing, network quality of service analysis and network optimization. The tool proposed will provide detail analytical results using drive test data. Also optimization techniques and solutions after processing Drive Test data obtained from a live LTE network shall be proposed. For this study, DT data from a mobile operator will be analyzed in details using the poposed tool, and how this analysis results can be used to identify poor performance and quality of service areas in the network. Then following optimization techniques proposed, how defined solutions and strategies can be applied to improve performance of these areas based on current network configurations.